Analysis of Mindfulness Practices Using Electroencephalogram (EEG) Interaxon Muse™ Headband Against the Concept of Self-Acceptance of Poststroke Clients - Sulaiman Girivirya (Global Writing Academica Researching and Publishing, 2023)
The Buddhist guidance and counseling model was applied to a client who experienced post-stroke 3 stress disorder and was isolated at the start of the Covid-19 pandemic in 2020. Mindfulness of breathing, body and mind activities is very important in mindfulness practice. Mental relaxation treatments and measurements were administered using the first generation Muse™